Comparison and Evaluation of Real-Time PCR, Real-Time Nucleic Acid Sequence-Based Amplification, Conventional PCR, and Serology for Diagnosis of Mycoplasma pneumoniae - Templeton, Kate E. (American Society for Microbiology, 2003)
Mycoplasma pneumoniae is a common cause of community-acquired pneumonia and lower-respiratory-tract infections. Diagnosis has traditionally been obtained by serological diagnosis, but increasingly, molecular techniques have been applied. However, the number of studies actually comparing these assays is limited. The development of a novel duplex real-time PCR assay for detection of M. pneumoniae in the presence of an internal control real-time PCR is described. In addition, real-time nucleic acid sequence-based amplification (NASBA) on an iCycler apparatus is evaluated. These assays were compared to serology and a conventional PCR assay for 106 clinical samples from patients with lower-respiratory-tract infection. Of the 106 samples, 12 (11.3%) were positive by all the molecular methods whereas serology with acute sample and convalescent samples detected 6 (5.6%) and 9 (8.5%), respectively. Clinical symptoms of the patients with Mycoplasma-positive results were compared to those of the other patients with lower-respiratory-tract infections, and it was found that the results for mean lower age numbers as well as the presence of chills, increased erythrocyte sedimentation rate, and raised C-reactive protein levels showed significant differences. Molecular methods are superior for diagnosis of M. pneumoniae, providing more timely diagnosis. In addition, using real-time methods involves less hands-on time and affords the ability to monitor the reaction in the same tube.